Persuasive Communication on Independent Food Resilience Awareness Through Indigenous-Based Bulekungdamber Training for the Residents of Kampung Landeuh, Bojong, Menteng Village, Leuwidamar, Lebak, Banten - Simamora, Santa Lorita; Pandjaitan, Rosmawaty Hilderiah; Sabena, Sabena (Universitas Pahlawan Tuanku Tambusai, 2025)
Persuasive Communication and Awareness of Independent Food Resilience Through Training in Catfish and Water Spinach Cultivation in Buckets (Bulekungdamber) Based on Indigenous Knowledge for the Residents of Kampung Landeuh, Bojong Menteng Village, Leuwidamar, Lebak, Banten, namely, the Village Government of Bojong Kampung. Encourage the creation of food independence from the people of Landeuh Village through the use of yards and non-productive land. Reducing dependence on food supplies from outside the village, while increasing local food security. Training is done ground, interactively, and can be practiced directly. A short Interactive Lecture using easy-to-understand language to describe food security and the benefits of self-sufficiency. Simple applied communication techniques interspersed with quesiont and answer so that citizens feel involved. Shows directly how to make a simple bioflok, grow vegetables in a polybag, or make liquid organic fertilizer. Next, discuss with the trainees until they understand.